ANALISIS PENGARUH DER DAN INTENSITAS R&D TERRHADAP NILAI PERUSAHAAN (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE TAHUN 2008-2011) - YULIANA, TANTI (Jurnal Akuntansi AKUNESA, 2013)
The purpose of this research to determine the effect from debt to equity ratio andR&D intensity either simultaneously or partially on value of the firm inmanufacturing firm. Method used in this research is descriptive kuantitative. Theanalytical method used is multiple linear regression analysis. Partially, based on thetest results of this study indicate that the independen variables are debt to ratio hadno significant effect on value of firm, although R&Dintensity had significant effect onvalue of the firm. Simultaneously DER and R&D intensity have a significant effect onvalue of the firmKeywords: debt to ratio, R&D intensity,value of the firm